Internet Protocol Based Satellite On-Board System - Emir Husni; Nazmi Febrian; Angga Putra (Universitas Ahmad Dahlan, 2016)
The reliability of satellite data communication can be enhanced by designing two subsystems involving data communication among subsystem and data communication between satellie and Ground Station (GS). In this paper, Error Control Coding (ECC) is applied in satellite data communication with Automatic Repeat Request (ARQ) method. Further, bit error checking uses the calculation of 15 bit Cyclic Redundancy Check (CRC) Controller Area Network (CAN) standard. The calculation of CRC is attached in CAN frame over IP communication protocol between primary OBC and secondary OBC. OBC is designed by implementing Triple Modular Redundant system on a Linux-based operating system. The CAN frame over IP simulation with manual input is found to correct all corrupted data. When the simulation uses NetEM, the system corrects 100 % data with 0-10 % value of corruption with maximum time transfer of 84.472 seconds. ION DTN is also found to correct all corrupted data with values from 0 to 2 % and maximum delay at an altitude of 50,000 kilometer orbit using NetEm for TMTC mission. The testing results show that the system will keep carrying out its mission as long as a fault does not occur on all three OBC at the same time.